Chaperoning the DNA damage response. (August 2017) - Stracker, Travis H.
Abstract : The NBN component of the MRE11‐RAD50‐NBN (MRN) complex and the ATM kinase have been identified as clients of the HSP90α chaperone. Inhibition of HSP90 leads to reduced stability of NBN and ATM and an impaired DNA damage response. These results identify new regulatory details of the DNA damage response and further explain the chemosensitizing effects of HSP90 inhibitors.